Altitude and particle size measurements of noctilucent clouds by RGB photometry radiative transfer and correlation analysis. (February 2023) - Ugolnikov, Oleg S.
Highlights: A technique for simultaneous measurements of altitude and mean particle size of noctilucent clouds is developed. Results are confirmed by radiative transfer analysis. Method was applied to the observations of bright clouds in summer 2020-2022. Abstract: Bright noctilucent or polar mesospheric clouds are frequently observed during the recent years. The study of possible reasons and relations with climate change requires data on long-time trends of mean particle size and altitude. Extended worldwide observational data is a good tool for this, and it can be provided by simple RGB-photometry using widely distributed all-sky cameras. Based on observations of bright expanded clouds in summer 2020-2022, the method of mean particle size determination is suggested, results are validated using a radiative transfer model. The procedure also allows finding the effective "umbral" altitude of clouds. The correlation of size and altitude of particles is compared with existing lidar data and models of particle growth.